Latino Students Patient Safety Questionnaire: cross-cultural adaptation for Brazilian nursing and medical students - Aline Carrilho Menezes; Carolina de Sousa Penha; Fabrícia Moreira Amorim Amaral; Adriano Marçal Pimenta; Helen Cristiny Teodoro Couto Ribeiro; Adriana Silvina Pagano; Luciana Regina Ferreira da Mata
ABSTRACT Objectives: to perform a cross-cultural adaptation of the Latino Student Patient Safety Questionnaire for Brazilian Nursing and Medical students. Methods: methodological study carried out in six stages - forward translation, synthesis, back-translation, expert committee assessment, pre-test and reporting to the authors of the original instrument. Data at the expert committee and pre-test stages were collected and analyzed using the web platform e-Surv. The level of agreement adopted for the expert committee evaluation with 20 participants and the pre-test evaluation with 38 students was ≥ 90%. Results: the first evaluation round by the expert committee showed a <90% agreement for 21 out of the 26 questionnaire items, requiring adjustments. In the pre-test, three items in the instrument reached a <90% agreement and were revised to obtain the final version. Conclusions: the Brazilian version of the Latino Student Patient Safety Questionnaire instrument was considered culturally adapted to Brazilian Portuguese.